PROMISING THE SELF-SELF- TRAINING, TRAINING, IMPROVING QUALITY AND CAPACITY OF THE LEADERS AND MANAGERS IN VIETNAM - Nguyen , Thi Thao; Nguyen, Hoang Phuong (International Journal of Psychosocial Rehabilitation, 2020)
Leaders and managers are those who are elected and appointed to key positions, hold high positions in agencies and organizations of the political system, who are empowered, authorized and exercise political power, state power. However, when there is power, a part of leading and managing officials abuse power, abuse power, transgress rights, decline in political thought, morality, lifestyle, violate Party discipline and law gorvernment's. To overcome that situation, each leading and managerial staff must regularly and seriously cultivate and train themselves in order to improve their quality and capacity. Refresher training activities must be carried out in all aspects, in the entire leadership, management activities and in association with daily life and activities. It is both a requirement, a duty, a responsibility to the Party, to the people of each leader and manager, as well as an effective way to implement the role model, requiring determination and perseverance. and persistent implementation. In the current period, in order to promote the self-discipline, to train and improve the quality and capacity of leaders and managers, it is necessary to combine and implement many solutions from the officials themselves. lead, manage and promote the role of party committees and party organizations, both the political system and the people in examining and supervising the training and training of leaders and managers.